Type 2 diabetes control and complications and their relation to serum magnesium level - Khaled Alswat (Archives of Medical Science, 2021)
Introduction Type 2 diabetes (T2D) is a growing health problem nationally and worldwide. Magnesium is an important mineral that is essential for a wide range of metabolic reactions. Here, our primary goal was to determine the prevalence of hypomagnesemia and its relationship to glycemic control, cardiovascular markers, and T2D-related complications.